The impact of contemporary communication methods in project work on students’ academic writing development in scholarly community contexts - Gulieva, Elnara Fakhretdinovna (The Lingua Spectrum, 2026)
The article explores contemporary communication methods in project-based learning as an important means of developing students’ academic writing within academic and research communities. It focuses on the use of digital platforms, online collaboration tools, synchronous and asynchronous communication, and shared writing technologies in educational projects. The study argues that integrating project-based learning with modern communication technologies improves students’ academic argumentation, critical analysis of sources, reflective thinking, and adherence to academic discourse conventions. The methodological approach includes theoretical analysis of academic literature, generalization of pedagogical experience, and comparative analysis of traditional and digital academic interaction. The findings reveal key mechanisms through which project communication enhances academic writing quality and promotes students’ engagement in academic and professional communities. The article concludes that systematic use of modern communication methods in project-based learning is essential for the sustainable development of students’ academic writing competence and academic culture in higher education institutions.